Estrés laboral frente al desempeño de los trabajadores de la empresa de telecomunicaciones “Telconet Latam” sucursal Loja en la actualidad. - Yaguana Gaona, Nancy Paola (2024)
Work stress is one of the most frequent problems in workers due to several work-related factors which have repercussions on their well-being and performance. The main objective of this research was to analyze the causes and effects of work stress on workers of the company “Telconet Latam” Loja branch and its impact on current job performance. Likewise, the specific objectives consisted of: identifying the theoretical foundations of work stress; analyzing the impact of work stress on individual and collective performance levels of employees; finally, designing an intervention proposal to mitigate work stress and improve the well-being and performance of workers. The research was carried out with a qualitative approach, using a deductive method, the design was non-experimental, the techniques used were documentary type with its bibliographic review matrix instrument; survey with the questionnaire instrument designed in Google Forms; finally, collecting, planning and designing whose instrument was the intervention proposal report. The population under study consisted of 80 workers from the company “Telconet Latam” Loja branch. The results obtained reveal that the company's workers indicate that the main factors causing work stress are excessive workload, deadlines to complete their tasks, and demands to deliver results, affecting their well-being and performance. It is concluded that work stress is an existing problem among the company's workers, and that it also produces negative effects at an individual and collective level, which causes a decrease in the company's productivity, highlighting the need to create and implement strategies that address this problem.